Performance Evaluation of WirelessLocal Area Network - Elia Hallaji, Rasha Albert (Nahrain University College of Engineering Journal, 2008)
The enormous growth of public mobile communications and the tendency to provide similar wireless services in indoor environment reacts on the activities in the area of widebandwireless local access, and Wireless Local Area Networks (WLAN) architectures and protocols. The IEEE 802.11 WLAN standard has beendeveloped to provide high bandwidth to mobile users in a short-range indoor environment. Apart from mobility, it should provide some QoS guarantees, for certain set of services. In this paper, wireless computer network was constructed and analyzed according to standard IEEE 802.11b with its two channelrates 1Mbps and 11Mbps using OPNET ITGuru Simulator. The physical layer at the radio-interface supports three different coding techniques: Frequency Hopping Spread Spectrum (FHSS), Direct Sequence Spread Spectrum (DSSS) and Infrared (IR). The present model considers DSSS coding. The system utilizes the behavior of the IEEE802.11b WLAN within single Basic Service Set (BSS). The BSS consists of 5-20 stations, which is a reasonable size of the WLAN. Each stationperforms access to the network using the Distributed Coordination Functionality only. The observed performance measures are defined as follows: - Throughput is the average number of successfully transmitted bits per second. - Delay is defined to be the elapsed time between the moments of packet arrival at the station queue and positive acknowledgment reception for the corresponding frame, averaged over all successfully transmitted frames.It is concluded that, the simulation s results show that the model performs as expected and emonstrates the performance of different traffic types under different network configurations for the selected workload